'A more colorful picture of my own vision': expansive learning in Puerto Rico's student anti-austerity movement. (3rd May 2020) - Laguarta Ramírez, José A.
ABSTRACT: Social movement scholars have long been aware of leadership competition or 'factionalism' as one of the mechanisms within the longer process of polarization. As such, competition is often discussed as a harbinger of de mobilization, and rarely in the context of movement emergence or growth. In turn, education scholars have examined social movement learning primarily as a cognitive process of identity formation, with rare and oblique references to the literature on movement dynamics. The first phase of the 2010–2011 student strike at the University of Puerto Rico (UPR) is a useful counterintuitive case for re-examining these conventional wisdoms, as existing studies and first-hand accounts suggest a pattern of intimate connections between factional competition and movement learning. In this article, I propose Cultural Historical Activity Theory (CHAT) as an alternative framework for analyzing that sequence. By recasting competition and other movement dynamics as aspects of the internal contradictions of nested activity systems, themselves crucial to the emergent process of expansive learning, CHAT may help bridge the gap between fields and approaches.